Transcriptome analysis of genes involved in the pathogenesis mechanism of potato virus Y in potato cultivar YouJin - Yang, Tianqi; Zhao, Xingyue; Bai, Jinjiang; Lv, Wenxia; Chen, Qi; Hu, Jun; Liu, Guangjing; Zhao, Yuanzheng; Zhou, Hongyou; Zhao, Mingmin; Zheng, Hongli (Frontiers in Microbiology, 2024)
Potatoes (Solanum tuberosum L.) can be infected by various viruses, but out of all of them, the potato virus Y (PVY) is the most detrimental. Research shows that the potato cultivar YouJin is especially vulnerable to PVY and displays severe symptoms including leaf vein chlorosis, curled leaf margins, large necrotic spots on the leaf blades, and the growth of small new leaves. Transcriptome analysis of differential genes was conducted in this study to examine the pathogenesis of PVY on YouJin. Results showed that 1949 genes were differentially regulated, including 853 up-regulated genes and 1096 down-regulated genes. Gene Ontology(GO) and Kyoto Encyclopedia of Genes and Genomes(KEGG) enrichment analysis indicated that carbohydrate synthesis and metabolism pathways were suppressed, and electron transferase and hydrolase activities were reduced. Moreover, there were increased expression levels of protein kinase genes. By focusing on plant-pathogen interaction pathways, six core genes all up-regulating the WARK family of transcription factors were obtained. Additionally, a constructed PPI network revealed the identification of key modular differential genes, such as down-regulated photosynthesis-related protein genes and up-regulated AP2/ERF-ERF transcription factors. Functional network enrichment analysis revealed that PVY infection limited RNA metabolism, glutathionylation, and peroxiredoxin activity while triggered the expression of associated defense genes in YouJin. After analyzing as above, twenty-six DEGs were screened and confirmed via RT-qPCR. These results establish a hypothetical framework for clarifying the pathogenesis of PVY in the YouJin variety of potatoes, which will help design the disease resistance of YouJin.